Decision-making in stem cell trials for spinal cord injury: the role of networks and peers. (July 2012) - Eijkholt, Marleen; Kwon, Brian K; Mizgalewicz, Ania; Illes, Judy
Aims: The purpose of this study was to characterize the self-perceived role of professionals and personal caregivers in decision-making about participation in stem cell clinical trials by individuals in early post-spinal cord injury time-points.Materials & methods: Data were obtained from focus groups and semi-structured individual interviews from two networks: healthcare professionals (e.g., physicians, allied healthcare workers) and personal contacts (family and friends). We transcribed audio-recorded data in extenso and analyzed transcripts using the qualitative method of constant comparison.Results: Results from more than 60 h of data suggest that adequate decision support is difficult to achieve for individuals during the subacute phase of injury. Three major obstacles prevent this goal: the personal dimensions of risk; limited insights into the pathophysiology and recovery process; and deference of each network to the other.Conclusion: The data suggest that novel strategies for decision-making processes, such as those involving peer support, are needed to enrich the knowledge base of all stakeholders. The results further underscore the importance of the role that both the academic and private sector play in ensuring the protection of human subjects in these trials. Original submitted 30 January 2012; Revised submitted 18 April 2012